PEDAGOGICAL FOUNDATIONS OF DEVELOPING CRITICAL THINKING OF PRIMARY SCHOOL STUDENTS - Latipova Ma’rifat Salohiddin qizi (International Multidisciplinary Journal for Research & Development, 2024)
This article analyzes the development of critical thinking of elementary school students as a psychological-pedagogical research problem. The development of critical thinking skills increases students' ability to solve complex problems, think logically and make independent decisions, so these skills are an integral part of the educational process. The article examines various methods of developing critical thinking, including pedagogical approaches, the use of technology, social interaction, and the organization of the learning environment.